Biorhizome: A Biosynthetic Platform for Colchicine Biomanufacturing - Sivakumar, Ganapathy; Alba, Kamran; Phillips, Gregory C. (Frontiers in Plant Science, 2017)
Colchicine is one of the oldest plant-based medicines used to treat gout and one of the most important alkaloid-based antimitotic drugs with anticancer potential, which is commercially extracted from Gloriosa superba. Clinical trials suggest that colchicine medication could prevent atrial fibrillation recurrence after cardiac surgery. In addition, therapeutic colchicine is undergoing clinical trials to treat non-diabetic metabolic syndrome and diabetic nephropathy. However, the industrial-scale biomanufacturing of colchicine have not yet been established. Clearly, further studies on detailed biorhizome-specific transcriptome analysis, gene expression, and candidate gene validation are required before uncover the mechanism of colchicine biosynthesis and biorhizome-based colchicine biomanufacturing. Annotation of 32312 assembled multiple-tissues transcripts of G. superba represented 15088 unigenes in known plant specific gene ontology. This could help understanding colchicine biosynthesis in G. superba. This review highlights the biorhizomes, rhizome specific genes or gene what expressed with high level in rhizomes, and deep fluid dynamics in a bioreactor specifically for the biomanufacture of colchicine.